Memetakan Visi Prabowo Gibran Pada Masa Kampanye Dalam Prespektif Pembangunan : (Analisis Wacana Kritis Visi Dan Misi Prabowo Gibran Dalam Prespektif Moderenisasi) - Nanda Aulia Rahmawati; Shalfian Agung Prasetyo; Muhammad Wildan Ramadhani (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This is an analysis using development theory related to Prabowo Subianto and Gibran Rakabuming Raka's campaign in the 2024 presidential election which uses Keritis Discourse Analysis, based on a linear view of economic growth which is based on modernization theory by taking four superior work programs. Government digitalization in Indonesia is considered a solution to increase the efficiency of public services, but challenges such as uneven development and limited human resources need to be overcome. Meanwhile, the plan to move the capital city by the Jokowi government and Prabowo's support shows a commitment to infrastructure development, but requires careful planning and serious handling of social, economic and environmental impacts. The maneuvers used by Prabowo emphasize strategic infrastructure development and improving the quality of human resources, while Gibran focuses on local economic empowerment and economic independence.